City Marketing Strategies and Their Impact in the Development of the City of Balad - Jamal, Abbas; Khairy , Areaj (Journal of Planner and Development, 2026)
In light of the growing urban challenges faced by developing cities, particularly in Iraq, city marketing has emerged as a promising strategic tool that can be employed to achieve sustainable urban development. This paper aims to analyze the impact of city marketing strategies on fostering sustainable urban development in the city of Balad, by drawing insights from successful global experiences in this field. The study is based on the hypothesis that the marketing strategies adopted in global cities such as Barcelona, Amsterdam, Dubai, and AlUla can be adapted and applied within the local context of Balad in a way that contributes to promoting sustainable urban development. The research adopts a descriptive-analytical methodology grounded in the review of relevant literature and previous studies, in addition to a comparative case study approach to analyze urban marketing strategies in the four selected cities and extract applicable lessons. The findings indicate that adopting urban marketing strategies based on local identity, promoting place branding, and activating community participation can significantly enhance the city's attractiveness and improve its quality of life. The study recommends developing a localized city marketing strategy for Balad, built upon its cultural, religious, touristic, and social assets, in order to achieve the goals of sustainable urban development.